Fluids and hyperosmolar agents in neurocritical care: an update. Issue 2 (April 2019) - Farrokh, Salia; Cho, Sung-Min; Suarez, Jose I.
Abstract : Purpose of review: To discuss recent updates in fluid management and use of hyperosmolar therapy in neurocritical care. Recent findings: Maintaining euvolemia with crystalloids seems to be the recommended fluid resuscitation for neurocritical care patients. Buffered crystalloids have been shown to reduce hyperchloremia in patients with subarachnoid hemorrhage without causing hyponatremia or hypo-osmolality. In addition, in patients with traumatic brain injury, buffered solutions reduce the incidence of hyperchloremic acidosis but are not associated with intracranial pressure (ICP) alteration. Both mannitol and hypertonic saline are established as effective hyperosmolar agents to control ICP. Both agents have been shown to control ICP, but their effects on neurologic outcomes are unclear. A recent surge in preference for using hypertonic saline as a hyperosmolar agent is based on few studies without strong evidence. Summary: Fluid resuscitation with crystalloids seems to be reasonable in this setting although no recommendations can be made regarding type of crystalloids. Based on current evidence, elevated ICP can be effectively reduced by either hypertonic saline or mannitol.